The water resources policy process in India: Centralisation, polarisation and new demands on governance - Peter P. Mollinga (University of Bonn, Center for Development Research (ZEF), 2005)
This paper reviews the literature on the characteristics of the post-Independence water resources policy process in India, with an emphasis on the recent period when critiques of existing and demands for new or adapted governance structures have become increasingly forceful. It will be shown that the dynamics of the water resources policy process has been studied to a very limited extent, compared to, for example, the study of (economic) impacts of policies and local-level water management practices. The first point the paper makes is that in an era of institutional transformation in the water sector, analysis of the actual dynamics of policy processes is required. The paper will sketch the 'policy as process' and 'politics of policy' perspectives from which such analysis could be undertaken. The paper then moves on to discuss certain main characteristics of the water resources governance structure and policy process in India. A first main characteristic is that of centralisation and hierarchy, rooted in the post-Independence planned development approach, the inherited structure of the government administration, the specific nature of the civil engineering dominated water resources bureaucracy and other factors, which have reproduced themselves in new forms and shapes under competitive populism, but are facing severe dilemmas and problems in the age of liberalisation. A second characteristic of the Indian water resources policy process is the high degree of polarisation in the debate and the interaction between civil society and the state. The Narmada and interlinking of rivers issues are cases in point, but it is a much broader phenomenon. This points to the absence of (effective) institutions for mediating water resources conflicts, particularly at the intermediate level. Great hopes are put by some on the decentralisation through the Panchayat Raj institutions. The paper argues that the PRI system and 'localist' approaches in general will be unable to address some of the core problems and issues in the water sector. The paper concludes with a research agenda for strategic analysis of policy processes in the water sector from a political economy of public policy perspective.
urn:nbn:de:0202-2008091160
Keywords: 330